Anatomical Predictors of Transcranial Surgical Access to the Suprasellar Space - Straus, David; Eddelman, Daniel B.; Byrne, Nika; Tchalukov, Konstantin; Wewel, Josh; Munich, Stephan A.; Kocak, Mehmet; Byrne, Richard (Journal of Neurological Surgery Part B: Skull Base, 2019)
Objective The suprasellar space is a common location for intracranial lesions. The position of the optic chiasm (prefixed vs. postfixed) results in variable sizes of operative corridors and is thus important to identify when choosing a surgical approach to this region. In this study, we aim to identify relationships between suprasellar anatomy and external cranial metrics to guide in preoperative planning.Methods T2-weighted magnetic resonance images (MRIs) from 50 patients (25 males and 25 females) were analyzed. Various intracranial and extracranial metrics were measured. Statistical analysis was performed to determine any associations between metrics.Results Interoptic space (IOS) size correlated with interpupillary distance (IPD; a = 7.3, 95% confidence interval [CI] = 4.5–10.0, R2 = 0.3708, p = 0.0009). IOS size also correlated with fixation of the optic chiasm, for prefixed chiasms (n = 7), the mean IOS is 205.14 mm2, for normal chiasm position (n = 33) the mean IOS is 216.94 mm2 and for postfixed chiasms (n = 10) the mean IOS is 236.20 mm2 (p = 0.002). IPD correlates with optic nerve distance (OND; p = 0.1534). Cranial index does not predict OND, IPD, or IOS.Conclusion This study provides insight into relationships between intracranial structures and extracranial metrics. This is the first study to describe a statistically significant correlation between IPD and IOS. Surgical approach can be guided in part by the size of the IOS and its correlates. Particularly small intraoptic space may guide the surgeon away from a subfrontal approach.
Keywords: suprasellar; intraoptic space; subfrontal approach; transsylvian approach